The importance of attachment in child development - Dreyfus Vallejos, Hortensia (2019)
The aim of this article is to conduct a review of attachment theory, by synthesizing information from some authors who address that theory; demonstrating how an inappropriate attachment could be the cause of several pathologies; addressing briefly its relationship with neurosciences, with constructed mental representations, with the crossgenerational transmission of attachment, and with resilience. Attachment has been studied, consolidated and enriched over time by several researchers -which will be indicated in our work- due to the importance of the existing theory in relation to the influent emotional bond that is established between the mother and/or significant person and the child, concluding that an adequate attachment or a parenting style with attachment or respectful parenting in the child’s development will allow productive people, with easy adaptation and socially competent.